REAKSI PASAR MODAL SYARIAH INDONESIA TERHADAP PERISTIWA POLITIK ( Event Study pada Peristiwa Kemenangan Donald Trump Sebagai Presiden Amerika Serikat Ke - 45) - Nugrahani, Cahaya; Jati, Agung Nugroho (KIAT BISNIS, 2017)
This study aims at market reaction shown by the average difference of Jakarta Islamic Index (JII) to a political event that is the election of Donald Trump to become the 45th president of the United States. This study is an event study and the event is a Donald Trump Victory event of Quick Count, Donald Trump Inauguration Event as 45th President of the United States and Prime State of Donald Trumps Country Speech as the 45th President of the United States. The sample of this research is JII at day closing for three days before and three days after the event. The results concluded that Donald Trumps quick count events and the inauguration of Donald Trump as the 45th President of the United States responded to the market with negative sentiments, as evidenced by a drop in the index of 2.05% and 1.79%. While the incident of Prime Minister of State Donald Trump as President of the United States to-45, not responded by the market. Keywords : Jakarta Islamic Index, market reaction, political events